On the bending strength of ZnO nanowires - Lu, Chungsheng (Elsevier, 2008)
Compared to bulk samples, the bending strength of ZnO nanowires exhibits nearly two orders of magnitude increase and approaches their theoretical value. Statistical analysis on the scatter strength data of ZnO nanowires by using three versatile distributions has shown that, in contrast to Young's modulus, no obvious size effect was observed, and the bending strengths were insensitive to aspect ratios and flaws at the nanoscale. The reasons for this surprising tolerance behavior can be explained by the collective interaction of "flaws" in a nontraditional sense.